Experiences in the Gulf of Mexico: Overcoming Obstacles for Commercial Fishing Occupational Safety and Health Research. Issue 4 (2nd October 2019) - Levin, Jeffrey; Carruth, Ann; Bui, Thu; Perkins, Robert; Gilmore, Karen; Wickman, Amanda
ABSTRACT: Researchers involved in community-based participatory research often face challenges due to numerous dynamic factors, including the physical location of the study population, willingness to participate, language barriers, cultural norms, social stigmas, and unpredictable weather and other disasters. Investigators who work with commercial fishermen are all too familiar with these potential obstacles and barriers to performing occupational safety and health research. Such has been the case along the Texas and Louisiana gulf coasts, where the burden of occupational fatalities in the shrimp fishery remains high. Moreover, the need for strategic community, regulatory agency, and research partnerships in order to explore solutions that can help to reduce this burden is ongoing. The IFISH 5 conference and the panel session described in this brief report offered a venue to acknowledge and create awareness of these barriers and opportunities for developing sustainable solutions that can have an impact on this loss of life. The approach taken was to explore the perspectives of a panel of regional collaborators including two researchers, an outreach community liaison, and a marine safety and health official from the U. S. Coast Guard. Key barriers emerging from the panel fell into four themes, each emphasized by one of the four panel members, allowing for discussion of potential solutions. The themes included: (1) language gap; (2) cultural influences and use of personal flotation devices; (3) relationships with the community; and (4) enforcement agency role as a trusted opinion leader. This panel session can readily serve as a model to promote similar exploration of barriers and solutions in commercial fishing across other regions of the US and internationally as well.